Structural insights into the allosteric site of Arabidopsis NADP-malic enzyme 2: role of the second sphere residues in the regulatory signal transmission - Gerrard Wheeler, Mariel Claudia (2021)
Fil: Fil: Gerrard Wheeler, Mariel Claudia. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Centro de Estudios Fotosintéticos y Bioquímicos (CEFOBI-CONICET); Argentina.